La gestión educativa en la participación de los padres de familia en una institución educativa pública del Distrito de San Clemente - Pisco - Yanccay Ortiz, Ayda (2022)
Every Educational Institution must know the management style that guides the progress of a school organization. In this way, they can design, establish and implement actions aimed at the achievement of quality education and the growth and constant improvement of the management team, since the great responsibility of marking the route of success of an educational management falls on them. Likewise, it is essential to know the types of parental participation in a school organization, since it influences the reciprocal work between managers, parents and the improvement of student learning. It is with this purpose that the following research question was raised: How is educational management related to the participation of parents in a public Educational Institution of the district of San Clemente, Pisco? The present study had as research objective: to analyze the relationship of educational management in the participation of parents in a Public Educational Institution of the district of San Clemente - Pisco. In this research, the quantitative method was improved, with a correlational descriptive design. As an instrument, a questionnaire previously validated by the experts was applied to measure the management styles and the types of participation of the parents. This questionnaire was applied to a sample of 44 teachers who work in the initial, primary and secondary levels of Regular Basic Education.